Three new synonymies and one new record of Thysanoptera (Insecta) from Mexico - Lima, Élison Fabrício Bezerra; Alencar, Áquila Rayane Silva De; Rodríguez-Arrieta, Jesús Alexander; Infante, Francisco (Zootaxa, 2025)
Based on the examination of Mexican material deposited in the Thysanoptera collection at IBUNAM, we propose three new synonymies: Solanithrips rubrus Johansen and S. strasseni Johansen as syn. nov. of Solanithrips halffteri (Johansen) and Adraneothrips falsus Johansen as syn. nov. of Bamboosiella cingulata (Hood). In addition, Oneilliella tica Lima, Vieira, O’Donnel & Mound is newly recorded in Mexico.